2002
DOI: 10.1074/jbc.m108760200
|View full text |Cite
|
Sign up to set email alerts
|

Transcytosis of Albumin in Astrocytes Activates the Sterol Regulatory Element-binding Protein-1, Which Promotes the Synthesis of the Neurotrophic Factor Oleic Acid

Abstract: We have recently reported that albumin, a serum protein present in the developing brain, stimulates the synthesis of oleic acid by astrocytes, which promotes neuronal differentiation. In this work, we gain insight into the mechanism by which albumin induces the synthesis of this neurotrophic factor. Our results show that astrocytes internalize albumin in vesicle-like structures by receptor-mediated endocytosis. Albumin uptake was followed by transcytosis, including passage through the endoplasmic reticulum, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
10

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 33 publications
3
73
0
10
Order By: Relevance
“…Although Mü ller cell transport of proteins secreted by other cells has not been shown before, it is known that glial cells, having an elaborate system for protein trafficking (Larocca and Rodriguez-Gabin, 2002), can deliver serum albumin across the blood-brain barrier into the gray matter (Tabernero et al, 2002). Our results suggest that Mü ller cells take in retinoschisin from their distal processes, and then deliver it into the inner retina where it interacts with bipolar cells (Reid et al, 2003) and other retinal components.…”
Section: Discussionmentioning
confidence: 98%
“…Although Mü ller cell transport of proteins secreted by other cells has not been shown before, it is known that glial cells, having an elaborate system for protein trafficking (Larocca and Rodriguez-Gabin, 2002), can deliver serum albumin across the blood-brain barrier into the gray matter (Tabernero et al, 2002). Our results suggest that Mü ller cells take in retinoschisin from their distal processes, and then deliver it into the inner retina where it interacts with bipolar cells (Reid et al, 2003) and other retinal components.…”
Section: Discussionmentioning
confidence: 98%
“…It might therefore be speculated that albumin contrary to ovalbumin might protect against cytokines through binding of fatty acids. Preincubation of INS-1E cells for 4 h with bovine serum albumin (11 mg/ml) for extraction and binding of fatty acids [14,35] or culture in serum free media did, however, not decrease the ensuing sensitivity to cytokines or affect the protective effect of albumin during cytokine exposure (results not given).…”
Section: Discussionmentioning
confidence: 65%
“…With plasma levels ranging from 35 to 50 mg/ml [10], albumin is the most important antioxidant in serum. In addition, albumin is also present at appreciable, although lower levels in the extra vascular compartment [11], and cellular uptake of albumin by receptor-mediated endocytosis is well documented [12][13][14]. In this context, albumin binding to cell surface receptors like megalin may protect from apoptosis through activation of intracellular signaling cascades and activate PI3K and/or p44/p42 MAPK as observed in some cell types [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 98%
“…It is shown that albumin affects metabolism of cultured astrocytes (Tabernero et al, 1999). Albumin up on transcytosis into cultured astrocytes stimulates the synthesis of neurotrophic factor oleic acid which promotes neuronal differentiation (Tabernero et al, 2002). Megalin is a receptor for albumin in astrocytes and is required for the synthesis of the neurotrophic factor oleic acid (BentoAbreu et al, 2008).…”
Section: Direct Neuroprotection By Albumin: Mechanismsmentioning
confidence: 99%